Was Jesus God? - Swinburne, Richard (Oxford : Oxford University Press, 2008)
Richard Swinburne argues compellingly that if there is a God, then the main doctrines which the Christian Church teaches about God are very probably true. In particular, he shows that there is strong philosophical support for the belief that Jesus, while remaining God, acquired a human nature and lived on earth for 30 years as a human being
God -- God is love -- God shared our human nature --God atoned for our wrongdoing -- God teaches us how to live -- God offers us heaven -- The life and death of Jesus -- The resurrection of Jesus -- Provisional conclusion -- The Church -- The Bible -- Final conclusion
Includes index
Keywords: Jesus Christ -- Person and offices; Incarnation -- Biblical teaching; Incarnation -- Philosophy